A phase 3 trial of azacitidine versus a semi‐intensive fludarabine and cytarabine schedule in older patients with untreated acute myeloid leukemia. Issue 12 (24th February 2021) - Vives, Susana; Martínez‐Cuadrón, David; Bergua Burgues, Juan; Algarra, Lorenzo; Tormo, Mar; Martínez‐Sánchez, María Pilar; Serrano, Josefina; Herrera, Pilar; Ramos, Fernando; Salamero, Olga; Lavilla, Esperanza; López‐Lorenzo, José L.; et al.
Abstract : BACKGROUND: Options to treat elderly patients (≥65 years old) newly diagnosed with acute myeloid leukemia (AML) include intensive and attenuated chemotherapy, hypomethylating agents with or without venetoclax, and supportive care. This multicenter, randomized, open‐label, phase 3 trial was designed to assess the efficacy and safety of a fludarabine, cytarabine, and filgrastim (FLUGA) regimen in comparison with azacitidine (AZA). METHODS: Patients (n = 283) were randomized 1:1 to FLUGA (n = 141) or AZA (n = 142). Response was evaluated after cycles 1, 3, 6, and 9. Measurable residual disease (MRD) was assessed after cycle 9. When MRD was ≥0.01%, patients continued with the treatment until relapse or progressive disease. Patients with MRD < 0.01% suspended treatment to enter the follow‐up phase. RESULTS: The complete remission (CR) rate after 3 cycles was significantly better in the FLUGA arm (18% vs 9%; P = .04), but the CR/CR with incomplete recovery rate at 9 months was similar (33% vs 29%; P = .41). There were no significant differences between arms in early mortality at 30 or 60 days. Hematologic toxicities were more frequent with FLUGA, especially during induction. The 1‐year overall survival (OS) rate and the median OS were superior with AZA versus FLUGA: 47% versus 27% and 9.8 months (95% confidence interval [CI], 5.6‐14 months) versus 4.1 months (95% CI, 2.7‐5.5 months; P = .005), respectively. The median event‐free survival was 4.9 months (95% CI, 2.8‐7 months) with AZA and 3 months (95% CI, 2.5‐3.5 months) with FLUGA ( P = .001). CONCLUSIONS: FLUGA achieved more remissions after 3 cycles, but the 1‐year OS rate was superior with AZA. However, long‐term outcomes were disappointing in both arms (3‐year OS rate, 10% vs 5%). This study supports the use of an AZA backbone for future combinations in elderly patients with AML. Abstract : Azacitidine improves 1‐year overall survival in comparison with a semi‐intensive chemotherapy schedule (FLUGA). The complete remission/complete remission with incomplete blood count recovery rate after 3 cycles is lower in an azacitidine arm than a FLUGA arm, but the best response achieved is similar for the 2 groups.